2002
DOI: 10.1530/eje.0.1470243
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of maternal serum fetuin/alpha2-HS-glycoprotein concentration with maternal insulin resistance and anthropometric parameters of neonates in normal pregnancy and gestational diabetes

Abstract: Objective: Human fetuin/a 2 -HS-glycoprotein (AHSG) is a 49 kDa serum and tissue protein which is a natural inhibitor of insulin receptor signaling. We investigated serum AHSG levels during pregnancy and whether the protein is involved in insulin resistance observed in healthy pregnant women and patients with gestational diabetes. Design: One hundred and four healthy pregnant women and 23 of their neonates, 30 patients with gestational diabetes and their neonates and 30 healthy age-matched non-pregnant females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 19 publications
(17 reference statements)
3
65
1
1
Order By: Relevance
“…We have found earlier that AHSG along with tumor necrosis factor-a and leptin may negatively regulate neonatal skeletal development. 35 In a recent study, no significant differences were observed in maternal, fetal and neonatal AHSG concentrations between pregnancies with normal and asymmetrically restricted fetal growth, 34 which is consistent with our findings. Beyond its concentration, the post-translational modifications of the protein (phosphorylation and glycosylation) can also influence the biological activity of AHSG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have found earlier that AHSG along with tumor necrosis factor-a and leptin may negatively regulate neonatal skeletal development. 35 In a recent study, no significant differences were observed in maternal, fetal and neonatal AHSG concentrations between pregnancies with normal and asymmetrically restricted fetal growth, 34 which is consistent with our findings. Beyond its concentration, the post-translational modifications of the protein (phosphorylation and glycosylation) can also influence the biological activity of AHSG.…”
Section: Discussionsupporting
confidence: 92%
“…33,34 Our research group has previously reported that serum AHSG concentration increases with advancing gestation in normal pregnancy. 35 According to our findings, the maternal systemic inflammatory response, which involves an acute-phase reaction, accounts-at least partly-for the decreased serum AHSG levels in preeclampsia, as suggested by the significant inverse correlation with serum CRP concentrations. In fact, circulating AHSG levels decrease in several conditions characterized by tissue damage, infection, inflammation or malignancy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This is an important indicator that AHSG is involved in the insulin signaling pathway. Furthermore, it appears to boost the likelihood of developing gestational diabetes during pregnancy (Srinivas et al, 1993;Kalabay et al, 2002;Swallow et al, 2004;Stefan et al, 2006;Briana et al, 2008). In fact, our results show that serum AHSG levels were increased in the PE group as determined by both the SRM assay ( Figure 3) and ELISA assay (Figure 4).…”
Section: Resultsmentioning
confidence: 61%
“…AHSG inhibits insulin-stimulated insulin receptor autophosphorylation, insulin-induced tyrosine phosphorylation of insulin receptor substrate-1 (IRS1), and the association of IRS1 with the p85 subunit of phosphatidylinositol-3 kinase in vitro (1-3). Elevated plasma AHSG was associated with insulin resistance in humans (4), and AHSG levels were higher in subjects with impaired glucose tolerance (5) and women with gestational diabetes (6). Ahsg knockout mice demonstrate increased basal and insulin-stimulated insulin receptor phosphorylation, increased glucose clearance, and insulin sensitivity (7).…”
Section: Research Design and Methods-mentioning
confidence: 99%